Effects of Particle Gradation, Relative Density and Curing on the Strength of Silicate Grouted Sand - Mollamahmutoglu, Murat; Avcı, Eyübhan (Springer, 2020)
This research paper presented the influence of variables such as sand gradation, relative density, curing time and condition and sodium silicate content on the strength characteristics of sodium silicate-formamide injected sand. To start with, the viscosity, gel time, and syneresis of sodium silicate-formamide grouts were studied. With the increase of sodium silicate content in the grout mix, the setting time of sodium silicate-formamide solutions decreased but the viscosity increased. Additionally, an increase in silicate content increased the amount of syneresis of grouts up to a specific point. The grouts with various silicate contents successfully penetrated the sand specimens with different grain size distributions and relative densities. The wet-cured and the air-dried samples were subjected to unconfined compressive (UC) and undrained-unconsolidated (UU) triaxial tests at various time intervals. The UC strengths of wet-cured as well as the air-dried specimens varied from 0.11 to 0.80 MPa and from 0.48 to 2.52 MPa respectively at the end of the 150th day. Moreover, as the internal friction angles of wet-cured and air-dried specimens ranged from 36 degrees to 43 degrees and from 41 degrees to 50 degrees the cohesion intercepts of wet-cured and air-dried specimens varied from 40.78 to 161.68 kPa and from 85.84 to 348.62 kPa respectively at the end of 150th day. As the silicate content of grouts increased, UC and UU strengths of air-dried and wet-cured samples increased. The UC and UU strengths of injected sand specimens under wet-cured condition reduced with time owing to syneresis. However, the UC and UU strengths of grouted specimens under air-dried condition increased with time. Though the strength of grouted sand samples was slightly increased with the increase of relative density, it was found to be highly variable with the grain size distribution.
Keywords: Chemical grout; Sand gradation; Relative density; Strengths; Curing condition